INTERNATIONAL JUDICIAL COOPERATION IN THE APPLICATION OF LAW NO. 143/2000 ON THE PREVENTION AND COMBATING OF ILLICIT DRUG TRAFFICKING AND CONSUMPTION - Buneci, Petre (International Journal of Legal and Social Order, 2025)
International judicial cooperation plays an important role in the enforcement of Law No. 143/2000 on the prevention and combating of illicit drug trafficking and consumption, in particular the modern legal instruments used in the European and international context. The main cooperation mechanisms are presented—extradition, the European arrest warrant, letters rogatory, the European investigation order, and mutual recognition of confiscation orders—and the importance of police cooperation and information exchange through Europol, Interpol, and SELEC is highlighted. Thus, current challenges related to legislative differences, data protection, and the complexity of evidence in transnational cases can hinder cooperation. Future trends, such as the digitization of cooperation procedures, the possible extension of the competence of the European Public Prosecutor's Office (EPPO), and the reorientation of criminal policy towards alternative measures and public health policies, are solutions to ensure a faster, more effective, and balanced response to drug trafficking.